A literate South : reading before emancipation - Schweiger, Beth Barton (Yale University Press, 2019)
A pervasive assumption about the culture of the southern United States is that it is firmly rooted in an oral tradition, not a written one. Schweiger complicates our understanding of literacy and reading in the American South before emancipation by shedding light on literature's importance in helping the South preserve tradition, develop southern vernacular, and form a cultural identity. Schweiger explains how the "universal truth" of literacy's incompatibility with slavery hid readers in this region from their society and beyond, and obscured a rich literate tradition.